Regard sur les statuettes hindoues et bouddhiques en bronze d’Indonésie. Leur rôle pour la connaissance de la civilisation javanaise ancienne et ses liens avec l’Asie du Sud et du Sud-Est - Mathilde Mechling (Les Cahiers de l'École du Louvre)
Although Hindu and Buddhist bronze statuettes constitute one of the major vestiges of ancient Indonesian civilisation (fifth–sixteenth centuries), few researchers take an interest in them. Yet they are easily transportable objects that evidently played a role in the cultural exchanges between India and Indonesia during this period. The bronzes enable us to better understand the nature and directions of the religious and artistic exchanges in this part of Asia, where Buddhism and Hinduism greatly inspired the material culture. A comparative study of the styles and iconographies of the bronzes found in Indonesia and those discovered in India reveals the exact regions with which there was contact as well as the historical period. Thus, specialists initially thought that Indian culture had been transplanted to Indonesia, suggesting the passivity and the absence of modifications or innovations on the part of the receiving culture.